2010
DOI: 10.1159/000320606
|View full text |Cite
|
Sign up to set email alerts
|

A Pilot Study of Rituximab in Immune-Mediated Inner Ear Disease

Abstract: Immune-mediated inner ear disease (IMED) is a cause of rapidly progressive auditory dysfunction. Patients are often responsive to high-dose corticosteroids and the disease is believed to be mediated by an antibody to inner ear proteins. To date, no therapies have proven effective as corticosteroid-sparing agents. Rituximab is a monoclonal antibody that depletes B cells, resulting in a reduction in autoantibody production. For that reason, rituximab was evaluated in a small pilot study in patients with IMED to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
26
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(26 citation statements)
references
References 55 publications
0
26
0
Order By: Relevance
“…With respect to serial rituximab infusions, 5 of 7 patients maintained their postcorticosteroid improvement in the pure-tone audiogram at 24 weeks, suggesting certain benefits of this treatment [Cohen et al, 2011]. The number of subjects in these previous studies tended to be small, and the studies were not prospective or randomized in nature due to the rarity of AIED.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With respect to serial rituximab infusions, 5 of 7 patients maintained their postcorticosteroid improvement in the pure-tone audiogram at 24 weeks, suggesting certain benefits of this treatment [Cohen et al, 2011]. The number of subjects in these previous studies tended to be small, and the studies were not prospective or randomized in nature due to the rarity of AIED.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, small open-label studies have demonstrated certain benefits of an IT injection of infliximab (Remicade) and intravenous infusions of adalimumab and rituximab. These benefits range from maintaining the level of baseline hearing loss to the improvement of the AIED [van Wijk et al, 2006;Vergles et al, 2010;Cohen et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…One open-label study evaluated the effects of intravenous administration of the antiCD20 antibody rituximab combined with a steroid taper on PTA and WRS (36). Subjects were those suspected clinically of having AIED and who responded to a prednisone trial.…”
Section: Rituximabmentioning
confidence: 99%
“…Rituximab is a chimeric monoclonal antibody that binds to the CD20 receptor of B lymphocytes, thereby inducing apoptosis and reducing their number. The few studies that have used rituximab in AIED patients have yielded encouraging results [35,36] . However, more studies are needed for reliable conclusions to be reached.…”
Section: Infliximabmentioning
confidence: 99%